Memory and trauma in international relations theories, cases, and debates - Resende, Erica Simone Almeida; Budryte, Dovile (London Routledge, 2014)
"This work seeks to provide a comprehensive and accessible survey of the international dimension of trauma and memory and its manifestations in various cultural contexts"--
Includes bibliographical references (pages 231-270) and index.
Keywords: International relations -- Social aspects; Psychic trauma; Collective memory; Political Science / General; Political Science / History & Theory; Political Science / International Relations / General